Analisis Distribusi Sisa Hasil Usaha Pada Koperasi Konsumen Pegawai Dinas Kependudukan Dan Pencatatan Sipil DKI Jakarta 2024: Analysis of the Distribution of Residual Business Results at the Consumer Cooperative of Employees of the DKI Jakarta Population and Civil Registration Office 2024 - Pratama, Ivana Kalista Intan; Putri, Intan Febriana; Lestari, Amanda; Putri, Pebryanti Ananda (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the distribution mechanism of Surplus (SHU) at the KOPPEG Consumer Cooperative of the Population and Civil Registration Office of DKI Jakarta Province in 2024, evaluate its compliance with regulations, and formulate strategies for SHU improvement. The research employed a descriptive qualitative approach with data collection through in-depth interviews and documentation studies. Results showed that SHU in 2024 reached Rp 570,515,784, increasing 57.26% from the previous year. The SHU distribution mechanism complied with Law No. 25 of 1992 and the cooperative’s bylaws, allocating 60% to members (70% based on transaction participation, 30% based on capital contribution) and 40% for cooperative funds. Financial performance indicated healthy conditions with liquidity ratio of 284.75%, solvency ratio of 34.80%, and profit margin of 14.28%. The SHU distribution positively impacted member welfare, membership growth of 5.6%, and capital strengthening of 8.68%. SWOT analysis identified high dependency on the savings and loan unit (96.84%) as the main weakness. Strategic recommendations include business unit diversification, service digitalization, and credit risk management enhancement.